Dual‐Emitting Dihydrophenazines for Highly Sensitive and Ratiometric Thermometry over a Wide Temperature Range. Issue 15 (16th May 2018) - Shi, Lijiang; Song, Wenxuan; Lian, Cheng; Chen, Wei; Mei, Ju; Su, Jianhua; Liu, Honglai; Tian, He
Abstract: Achieving ratiometric thermometry with a single organic luminophore is a tempting but challenging task. Herein, three dihydrophenazine‐based ratiometric thermometers, namely DPC, DPSi‐1, and DPSi‐2, are facilely developed via the novel vibration‐induced emission (VIE) strategy. By elaborately introducing alkyl/siloxane chains to the dihydrophenazine core, these fluorophores exhibit as powder with low melting point or nonvolatile liquids, which emit temperature‐sensitive dual emissions: predominantly blue fluorescence (FL) at low temperature and chiefly orange‐red FL at high temperature. According to the VIE mechanism, high temperature activates the intramolecular motions, thus facilitates the excited‐state configuration transformation of the phenazine moiety from bent to planar, as confirmed by the molecular dynamics calculation. The invisible temperature information over a broad range from 5 to 135 °C can be vividly revealed by these VIE‐based ratiometric thermometers, with a high sensitivity (3.40% per °C), a wide linear response region (50–135 °C) and good reversibility, in a solvent‐free and naked‐eye observable manner. Very importantly, these thermometers can be coated onto any object surface for simple and fast large‐area temperature detection, demonstrating their superior practicability compared with other luminescent thermometers. The ratiometric thermometry scheme proposed here may offer new insights into developing thermometers for various applications. Abstract : Highly sensitive ratiometric thermometry is achieved with dual‐emitting dihydrophenazines over a broad range (5‐135 °C) in a solvent‐free and naked‐eye observable manner, by taking advantage of their vibration‐induced emission attribute. The ratiometric thermometers developed here can be coated onto any object surface for simple and fast large‐area temperature measuring, demonstrating their outstanding practicability.